A new species of Admesturius Galiano, 1988 from north Chile (Araneae: Salticidae: Amycoida) - Bustamante, Abel A.; Scioscia, Cristina L.; Casanueva, María E. (Zootaxa, 2014)
The Hurieae group was created by Simon (1901) and revised by Galiano (1987). This group includes the genera Admesturius Galiano; Atelurius Simon; Hurius Simon; Scoturius Simon and Simonurius Galiano. They are nested within the Neotropical clade Amycoida (Maddison & Hedin 2003), but their phylogenetic relationships among these genera are uncertain.